Developmental patterns and formation and evolutionary mechanisms of surface cracks induced by the mining of shallowly buried coal seams - Enke HOU; Jiaxin MU; Xiaoshen XIE; Dong FENG; Lei YANG; Yan LI; Tao HE; Kangguang BAO; Xiaosheng CHEN (Meitian dizhi yu kantan)
ObjectiveSurface cracks are recognized as one of the most common geologic hazards in coal mining areas in northern Shaanxi Province. These cracks directly cause damage to surface ecosystems. Furthermore, those penetrating fractures in the overburden act as primary channels for surface water to burst underground, threatening the safe production underground. MethodsThis study aims to further reveal the developmental patterns of surface cracks induced by the mining of shallowly buried coal seams and elucidate their formation and evolutionary mechanisms. To this end, this study investigated mining face 15218 and 25213 in the Hongliulin Coal Mine in northern Shaanxi. Specifically, the surface cracks in the mining face were comprehensively examined using methods including surface crack mapping, dynamic monitoring of cracks, and numerical simulations. Results and Conclusion The results indicate that the surface cracks caused by the mining of shallowly buried coal seams exhibited a C-shaped distribution overall. The developmental characteristics and locations of the surface cracks were closely related to landform types. Under the same mining conditions, the proportion of cracks with widths greater than 5 cm in areas with loess gullies was 2.15 times that in areas with sandy beaches, suggesting a significantly higher developmental degree of cracks in the former areas than in the latter areas. Besides, the boundary cracks of the mining face exhibited a significantly higher developmental degree than cracks within the mining face. Surface cracks induced by the mining of shallowly buried coal seams manifested two dynamic developmental characteristics: ahead of and lagging behind mining positions. Among them, the formation of surface cracks induced by mining along mining face 25213 lagged behind the mining position, with a lag distance of 6.49 m. In contrast, surface cracks induced by mining along mining face 15218 were formed ahead of the mining position, with a lead distance of 20.07 m. Cracks within the mining face exhibited four activity characteristics, while the boundary cracks only showed an activity characteristic of cracking, increase in length, and stability sequentially. The surface cracks exhibited overall activity time ranging from 4 days to 14 days. Compression zones, tension-compression transform zones, and tensile zones were formed near the surface of the goaves. As the mining face advanced, movement deformation and failure zones within the roof strata and on the surface constantly expanded forward. The surface subsidence-induced basins were slightly larger than the goaves, with a maximum subsidence coefficient of 0.82. Non-penetrating cracks were primarily formed when the tensile deformations of soils along the margins of surface moving basins exceeded their limited values. In contrast, penetrating cracks were formed by the connection between upgoing cracks within the overburden and surface cracks or by the direct connection between the upgoing cracks and the surface. As the mining of the mining face advanced, the cycle rupture of the main roofs caused the surface cracks to continuously expand forward. The characteristics of variations in the surface crack width were closely related to the complex movement of blocks on both sides of the cracks. The results of this study can serve as an important reference for the prevention and control of surface cracks in the mining areas of shallowly buried coal seams.